Before American History : Nationalist Mythmaking and Indigenous Dispossession - Mucher, Christen (Book collections on Project MUSE., 2022)
"This book argues that the current understanding of North America's past was created as a tool of nationalism, and that it required the misappropriation of Indigenous histories. In the United States and Mexico, the Indigenous past was repurposed as American history while at the same time used to erase and denigrate Native peoples, a legacy that continues when we repeat these narratives"--